PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN DAN SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN DESA DI KECAMATAN RUTENG KABUPATEN MANGGARAI - Yuliana Sueng; Sulaiman; Suryaningsi (Jurnal Akuntansi Universitas Muhammadiyah Kupang, 2020)
This study aims to 1) To determine the effect of the application of Government Accounting Standards on the Quality of Village Financial Statements in Ruteng District, Central Manggarai Regency. 2) To determine the effect of the Accounting Information System on the Quality of Village Financial Statements in Ruteng District, Manggarai Tenggah Regency. 3) To determine the effect of the application of Government Accounting Standards and Accounting Information Systems on the Quality of Village Financial Statements in Ruteng District, Central Manggarai Regency. The method used in this research is a quantitative approach, and the design used is a descriptive design. The data collection technique was carried out by distributing questionnaires in 10 villages, Ruteng District, Manggarai Regency. The number of samples in this study were 30 respondents using purposive sampling technique. The data analysis technique used multiple linear regression analysis, while for testing the data analysis used the validity test, reliability, normality, multi-colonaryity, heteroscedasitity, descriptive statistics, multiple regression analysis, coefficient of determination, t test and F test. The results of this study indicate that 1) The first hypothesis of this study is accepted, namely that the application of government accounting standards has a positive effect of 2.557 and 0.019 on the quality of financial statements. 2) The second hypothesis of this study is accepted, namely that the Accounting Information System has a positive effect of 4.296 and a significant 0.000 on the quality of village financial reports. 3) Simultaneously SAP and SIA have a positive and significant effect of 4,844 on the quality of village financial reports.